2009
DOI: 10.1080/09537100903096684
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence for a matrix metalloproteinase-2 (MMP-2)-dependent shedding of soluble CD40 ligand (sCD40L) from activated platelets

Abstract: Platelets are the major source of soluble CD40 ligand (sCD40L) in the blood. It has been demonstrated that CD40L is cleaved from the surface of activated platelets to release sCD40L. However, the enzyme involved in sCD40L shedding has not been identified yet. Using a panel of pharmacological inhibitors of serine, cysteine, aspartate, or metalloproteinases, preliminary evidence is presented for the hypothesis that matrix metalloproteinase-2 (MMP-2) might be the protease, primarily responsible for CD40L cleavage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…10,40 Notably, it was observed that administration of NSC23766 significantly decreased the sepsis-induced increase of MMP-9 levels in plasma, indicating that Rac1 might be an important regulator of systemic levels of MMP-9 in abdominal sepsis. It should be mentioned that two studies have reported that MMP-2 might promote platelet release of CD40L in vitro, 41,42 but levels of MMP-2 in the plasma are not elevated in abdominal sepsis. 10 The potential presence of MMP-9 in platelets has been a controversial subject in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…10,40 Notably, it was observed that administration of NSC23766 significantly decreased the sepsis-induced increase of MMP-9 levels in plasma, indicating that Rac1 might be an important regulator of systemic levels of MMP-9 in abdominal sepsis. It should be mentioned that two studies have reported that MMP-2 might promote platelet release of CD40L in vitro, 41,42 but levels of MMP-2 in the plasma are not elevated in abdominal sepsis. 10 The potential presence of MMP-9 in platelets has been a controversial subject in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that these findings do not exclude the possibility that other MMPs or proteases might also be involved in the regulation of platelet shedding of CD40L in sepsis. For example, two in vitro studies have reported that MMP-2 might promote platelet release of CD40L in vitro [18,42].…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) constitute a large family of more than 25 functionally related endopeptidases [15] with the capacity to cleave most matrix proteins as well as several non-matrix targets, including cytokines, chemokines, adhesion molecules, and surface receptors [16]. One study reported that inhibitors of glycoprotein IIb-IIIa inhibit release of sCD40L from activated platelets [17], whereas other investigators found that inhibition of MMP-2 [18] and MMP-9 [19] decreased platelet shedding of CD40L. In this context, it is interesting to note that previous studies have found that the levels of certain MMPs, in particular members of the gelatinase subfamily (MMP-2 and MMP-9), are elevated in the plasma of septic patients [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme responsible for CD154 shedding on the surface of activated platelets has been demonstrated previously (8), but little is known about this process regarding T-cells. The metalloproteinase ADAM10 has been highlighted as a possible candidate (13), albeit no direct demonstration of its implication in CD154 cleavage has been provided.…”
Section: Cd154 Shedding Is Mediated By Adam10 and Adam17-mentioning
confidence: 99%
“…Interestingly, the shedding of CD154 from platelets is triggered following its interaction with CD40, which is also expressed on platelets (7). Recent evidence supports the role of matrix metalloproteinase-2 (MMP-2) (8), in association with the ␣IIb␤3 integrin (9), in mediating the proteolytic cleavage of CD154 from activated platelets. Moreover, MMP-9 was also reported to be involved in the shedding of CD154 from platelets with Crohn disease.…”
mentioning
confidence: 99%